(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
After 2003 Iraq witnessed a rapid development in the number and kind of non-governmental organizations in addition to the increase in their sources.A lot of obstacles and constraints hinder the development of the said organizations and one of the most important and prominent obstacles is their administrative and accounting structure that affect directly on the existence, continuity and survival of these organizations.This research discussed the concept the non-governmental organizations and reaching the assessment of internal control System in these organizations. Therefore, the researcher has assessed the internal control System applied National Olympic Committee of Iraq. The study showed vulnerabilities in the internal control the said Committee, subject of this research, where these points has been mentioned in the chapter of Conclusions and then the recommendations and suggestions were offered for the purpose of save the funds and properties of the organizations and make sure of the best use of the resources in line with their purposes.